2004
DOI: 10.1038/sj.jhh.1001708
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related difference in regression of left ventricular hypertrophy with antihypertensive treatment: the LIFE study

Abstract: While left ventricular (LV) structure and function differ between hypertensive women and men, it remains unclear whether sex affects regression of LV hypertrophy with antihypertensive treatment. We analysed paired echocardiograms in 500 men and 347 women enrolled in the Losartan Intervention For Endpoint reduction in hypertension (LIFE) study at baseline and after 12 months of antihypertensive treatment with either losartan or atenolol. At enrolment, 177 women and 242 men were randomized to losartan-based trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 40 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Antihypertensive therapy, however, has been shown to have a better effect on left ventricular mass regression in hypertensive women than in corresponding men [28]. Female sex hormones are assumed to have a cardiovascular protective effect, although intervention data on the effect of hormone replacement therapy do not support this [29].…”
Section: Discussionmentioning
confidence: 99%
“…Antihypertensive therapy, however, has been shown to have a better effect on left ventricular mass regression in hypertensive women than in corresponding men [28]. Female sex hormones are assumed to have a cardiovascular protective effect, although intervention data on the effect of hormone replacement therapy do not support this [29].…”
Section: Discussionmentioning
confidence: 99%
“…Olivetti et al 30 demonstrated that aging in men, but not in women, causes significant myocyte cell loss, reactive cells hypertrophy, and a change in the proportion of mono‐ and binucleate myocyte. In pathologic situations, such as aortic stenosis 31,32 and essential hypertension, 33,34 women exhibit a more concentric remodeling with preserved systolic function. In this respect, the presence of hypertrophic reserve in females was verified in an experimental model by Tamura et al 35 …”
Section: Discussionmentioning
confidence: 99%
“…60 Several studies have shown gender difference in physiological and pathological remodelling associated with different cardiovascular diseases. [61][62][63] In addition, in failing human hearts, Guerra et al demonstrated that the female heart is protected, at least in part, from necrotic and apoptotic death. 64 Based on these observations, it is possible that female patients have a more favourable substrate for reverse remodelling during CRT.…”
Section: Cardiac Resynchronisation Therapymentioning
confidence: 99%